One size does not fit all: Evaluating disparities in lung cancer screening eligibility amongst the Hispanic population - Olazagasti, Coral; Ehrlich, Matthew; Seetharamu, Nagashree (Frontiers in Oncology, 2022)
Lung cancer (LC) is the leading cause of cancer death among Hispanic men. We assessed the tendencies for screening eligibility amongst Hispanic prior to LC diagnosis according to the NCCN and The USPSTF guidelines available at the time of diagnosis. We conducted an observational study in patients diagnosed with LC from 2016 to 2019. Charts were reviewed to assess their screening eligibility prior to LC. The chi-square test was used to examine the association between race and ethnicity with each screening criteria. A total of 530 subjects were reviewed, of which 432 were included in the analysis. One hundred fifty-three and 245 subjects were ineligible for screening under NCCN and USPSTF criteria prior to their LC diagnosis. Twenty-eight of the subjects who did not fulfill NCCN criteria identified as AA and 12 as Hispanic Forty and 20 of the USPSTF screening ineligible subjects identified as AA and Hispanic . There was a significant association between screening eligibility criteria in Hispanics, with 52% Hispanic subjects meeting NCCN criteria compared to only 20% who met USPSTF (p=0.0184). There was also a significant association between ethnicity and USPSTF eligibility criteria (p=0.0166), as 80% of Hispanic subjects were screening ineligible under USPSTF criteria compared to 56% of non-Hispanic or other. In our study, Hispanics had significantly lower tendencies of meeting the USPSTF LC screening eligibility criteria than non-Hispanics or other. Interestingly, a proportionally higher number of Hispanics who were ineligible under USPSTF criteria met NCCN criteria. These findings suggest that leniency in the screening criteria can possibly lead to earlier detection of LC in high-risk individuals. Recently, USPSTF has modified their criteria which may benefit more of these individuals. To improve rates of screening and overall mortality of minorities, organizations should continue to re-evaluate and liberalize their screening guidelines.